prove the following id

Asked by aanchal.padyal | 25th May, 2010, 10:03: AM

Expert Answer:

Taking out cosθ common we can write LHS,

cosθ(1/(1 - sinθ) + 1/(1 + sinθ)) =

cosθ(2/(1 - sin2θ)) =         

              ...using the identity a2 - b2 = (a + b)(a - b) and simplifying the fraction like 1/c + 1/d = (c + d)/cd

cosθ(2/cos2θ)) =

2/cosθ = 2 secθ = RHS.

Regards,

Team,

TopperLearning.

Answered by  | 25th May, 2010, 07:05: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.